A graded metamaterial for broadband and high-capability piezoelectric energy harvesting. (1st October 2022) - Zhao, Bao; Thomsen, Henrik R.; De Ponti, Jacopo M.; Riva, Emanuele; Van Damme, Bart; Bergamini, Andrea; Chatzi, Eleni; Colombi, Andrea
Abstract: This work proposes a graded metamaterial-based energy harvester integrating the piezoelectric energy harvesting function targeting low-frequency ambient vibrations ( < 100 Hz). The harvester combines a graded metamaterial with beam-like resonators, piezoelectric patches, and a self-powered interface circuit for broadband and high-capability energy harvesting. Firstly, an integrated lumped parameter model is derived from both the mechanical and the electrical sides to determine the power performance of the proposed design. Secondly, thorough numerical simulations are carried out to optimize both the grading profile and wave field amplification, as well as to highlight the effects of spatial-frequency separation and the slow-wave phenomenon on energy harvesting performance and efficiency. Finally, experiments with realistic vibration sources validate the theoretical and numerical results from the mechanical and electrical sides. Particularly, the harvested power of the proposed design yields a five-fold increase with respect to conventional harvesting solutions based on single cantilever harvesters. Our results reveal that by bridging the advantages of graded metamaterials with the design targets of piezoelectric energy harvesting, the proposed design shows significant potential for realizing self-powered Internet of Things devices. Highlights: Broadband and high capability design targets are achieved under low frequencies. The DC power output of the proposed design is evaluated with an integrated model. Spatial frequency separation and slow waves in the design are analyzed in detail. A near-milliwatt DC power output is realized with metamaterials for the first time.